Correction: Gd(iii)–Gd(iii) EPR distance measurements – the range of accessible distances and the impact of zero field splitting. Issue 27 (21st June 2016) - Dalaloyan, Arina; Qi, Mian; Ruthstein, Sharon; Vega, Shimon; Godt, Adelheid; Feintuch, Akiva; Goldfarb, Daniella
Abstract : Correction for 'Gd(iii )–Gd(iii ) EPR distance measurements – the range of accessible distances and the impact of zero field splitting' by Arina Dalaloyan et al., Phys. Chem. Chem. Phys., 2015, 17, 18464–18476.